Expanding the role of medical retina virtual clinics using multimodal ultra-widefield and optical coherence tomography imaging - Lee JX (Dove Medical Press, 2018)
Jing Xian Lee,1 Vina Manjunath,2 S James Talks2 1Faculty of Medicine, Newcastle University, Newcastle upon Tyne, UK; 2Newcastle Eye Centre, Newcastle Hospitals NHS Foundation Trust, Newcastle upon Tyne, UK Background: An increasingly elderly population with a corresponding increase in ophthalmic conditions has led to increased pressure on hospital eye services (HES). In this study, we evaluated the use of a medical retina virtual clinic (MRVC), which has expanded into assessing all new medical retina referrals, where the need for urgent treatment was not clear. Methods: Retrospective analysis of all new patients who were seen in the MRVC between April 2016 and May 2018. Pro forma sheets were used in the MRVC to record the patient history, visual acuity, and type of imaging required. Two consultants reviewed the completed pro formas and images and provided a final diagnosis and management plan. These results and reasons for face-to-face (F2F) clinic appointment requests were analyzed. Results: Six hundred ten new referrals were enrolled in the virtual clinic. The most common diagnosis was diabetic eye disease (59.9%). In the virtual clinic 44.1% were followed up, 28.1% were discharged, and 27.8% were booked an F2F clinic appointment (urgent/routine). The main reason for F2F clinic was to offer treatment. Urgent F2F appointments took place on average 11.9 days after virtual clinic attendance. In only two cases was the image quality felt to be inadequate to assess the retina. Conclusions: MRVC is an effective way of triaging medical retina referrals to allow those patients needing treatment to be seen promptly in the medical retinal service. The use of multimodal ultra-widefield and optical coherence tomography imaging allows assessment of a wide range of retinal pathologies and is a promising solution to alleviate the burden on HES. Keywords: virtual clinic, optical coherence tomography, macular degeneration, choroidal naevus, diabetic retinopathy, teleophthalmology